Development of Annona muricata Linn as green corrosion inhibitor under produced water: inhibition performance and adsorption model - Ayende; Riastuti, Rini; Soedarsono, Johny Wahyuadi; Kaban, Agus Paul Setiawan; Hikmawan, Mohammad Ikbal; Rahmdani, Rizal Tresna (Eastern-European Journal of Enterprise Technologies, 2023)
This work used soursop as a green corrosion inhibitor to protect API 5L Grade A from detrimental corrodent under produced water. Despite the effectiveness of inorganic inhibitors, recent evidence on their toxicity test suggests that implementing organic inhibitors is substantial to replace synthetic corrosion inhibitors. However, soursop utilization as a green corrosion inhibitor is poorly understood due to the lack of a comprehensive extraction mode and inhibitive mechanism. Several tests were conducted, including weight loss, potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS), to unveil the nature of corrosion inhibition. Fourier Transform Infra-Red Spectroscopy revealed the dominant functional groups to bind with the substrate. The potentiodynamic polarization results show that the inhibitor is a mixed-type inhibitor that influences the anodic and cathodic reactions. The weight loss test showcases the highest inhibition efficiency of 52.62 % upon adding 2 ml inhibitors upon eight observation days. The polarization and EIS results provide that the inhibitor reduces the corrosion rate with higher inhibition of 88.52 %. The mentioned result is associated with the attachment of non-polar and polar Annona muricata Linn functional groups. The primary functional group involves C=O, C‒C and –O.H., which actively bonded to the metal’s surface. The aromatic group at a wavenumber of 1,050 and 1,090 cm-1 shows ether’s presence and behaves as an adsorption center. In this work, combining three solvents, hexane, acetone, and ethanol, elicits the complete extraction of the predominant compound from soursop